2011
DOI: 10.1155/2011/925950
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Commercial Neem Extract to Earthworms (Pheretima peguana)

Abstract: The LC 50 of commercial neem extract (Sadao Thai III containing azadirachtin; NEEM) on filter paper in the earthworm Pheretima peguana at 48 h and 72 h was 3.79 and 3.33 µg cm −2 , respectively. In earthworms exposed to five NEEM concentrations from 0.39 (∼10% of 48-h LC 50 ) to 3.13 (∼80% of 48-h LC 50 ) µg cm −2 , the radial thickness of the epidermis and body wall significantly (P < .05) decreased, and thickness of intestinal epithelium increased but only at high doses, approximately 25-fold above the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…2.5 ppm concentration of dimethoate similar changes which found by [27] were serious disintegration of cell margins and fusion of cells in the epidermis even at low doses of 0.24 mg kg-1 of Hexavalent Chromium, the entire epithelium being disintegrated, the epithelial cell layer was completely lost in certain regions at 893 mg kg-1 of cr, Epithelial sloughing was apparent by the space created between the epithelium and the circular muscle layer and [28] found some erosion of epithelium, fibrotic changes in the circular muscle and longitudinal muscle were noted in the earth worm exposed to the vermicomposting of paper cup, Cell necrosis was observed during this period. In temple waste vermicomposting, and [28].found the neighboring cells in circular and longitudinal muscles to be discontinuous when Earthworms exposed to~80% LC50 for 48 h (Aza 3.13 μg cm−2) , separated by narrow to large gap junctions also [31] reported that the epithelium separating from the muscle layer of the earthworm when the exposure to Normal Versus and Nano Cupper Enriched Engine Oil Previous studies suggested that earthworm skin has direct contact to the contaminated soils and is considered as a significant route to uptake of toxicants [32,33]. Epidermis and cuticle represent a primary barrier that protects earthworm's body from the environment and are also responsible for the transport of ions, thus allowing/blocking xenobiotics to enter the body [34].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…2.5 ppm concentration of dimethoate similar changes which found by [27] were serious disintegration of cell margins and fusion of cells in the epidermis even at low doses of 0.24 mg kg-1 of Hexavalent Chromium, the entire epithelium being disintegrated, the epithelial cell layer was completely lost in certain regions at 893 mg kg-1 of cr, Epithelial sloughing was apparent by the space created between the epithelium and the circular muscle layer and [28] found some erosion of epithelium, fibrotic changes in the circular muscle and longitudinal muscle were noted in the earth worm exposed to the vermicomposting of paper cup, Cell necrosis was observed during this period. In temple waste vermicomposting, and [28].found the neighboring cells in circular and longitudinal muscles to be discontinuous when Earthworms exposed to~80% LC50 for 48 h (Aza 3.13 μg cm−2) , separated by narrow to large gap junctions also [31] reported that the epithelium separating from the muscle layer of the earthworm when the exposure to Normal Versus and Nano Cupper Enriched Engine Oil Previous studies suggested that earthworm skin has direct contact to the contaminated soils and is considered as a significant route to uptake of toxicants [32,33]. Epidermis and cuticle represent a primary barrier that protects earthworm's body from the environment and are also responsible for the transport of ions, thus allowing/blocking xenobiotics to enter the body [34].…”
Section: Discussionsupporting
confidence: 65%
“…reported that the Neighboring cells in circular and longitudinal muscles appeared discontinuous (separated by narrow to large gap junctions) of the earthworm Eisenia foetida (Savigny) due to the exposure to pesticide, profenofos, also [27] were found The circular and longitudinal muscle layer of the body wall of the Cr (VI) (Hexavalent chromium) treated Eudrilus eugeniae were also damaged as indicated by the loss of structural integrity and increased intercellular spaces the damage was more severe in those exposed to 893 mg kg-1. [28]. Found that the neighboring cells in circular and longitudinal muscles to be discontinuous, separated by narrow to large gap junctions when Earthworms (Pheretima peguana) exposed to 80% LC50 for 48 h (Aza 3.13 μg cm−2) from commercial neem extract At 0.1ppm there was vacuolated muscle fiber, vacuolated epidermis and destroyed epidermis, in contrast the nuclei gathered have found in vacuolated which in circular muscles of adult(fig.…”
Section: Discussionmentioning
confidence: 99%
“…Azadirachtin (Aza), as active ingredient of AIE, belongs to the organic compounds group known as tetranortriterpenoid and has known to act as an ecdysone blocker and an insect anti-feedant (Muangphra and Gooneratne, 2011). Matrine, one of the major active ingredient extracted from the traditional medicinal herb Sophora flavescens, has been known to be a very effective for botanical insecticide.…”
Section: Introductionmentioning
confidence: 99%